Directional electromagnetic steel sheet
Patent Information
- Application Number
- JP2022189574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-18
- Filing Date
- 2022-11-28
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-11-28
AI Technical Summary
【0024】 本発明によれば、低鉄損であり、かつ、高い透磁率と良好な磁歪特性とを有する方向性電磁鋼板を得ることができる。また、本発明の方向性電磁鋼板は、歪み取り焼鈍後にも低鉄損であり、かつ、高い透磁率と良好な磁歪特性とを有するので、変圧器、特に、巻鉄心変圧器などの鉄心材料として、極めて有利に用いることができる。
Smart Images

Figure 0007639805000018 
Figure 0007639805000019 
Figure 0007639805000020
Abstract
Description
[Technical field]
[0001] The present invention relates to a grain-oriented electrical steel sheet. [Background technology]
[0002] Grain-oriented electrical steel sheets are used, for example, as materials for the iron cores of transformers. In transformers, it is required to suppress energy loss, which is affected by the iron loss of grain-oriented electrical steel sheets.
[0003] Here, the iron loss of grain-oriented electrical steel sheet mainly consists of hysteresis loss and eddy current loss. Techniques developed to improve hysteresis loss include highly orienting the (110)
[0001] orientation, known as the GOSS orientation, in the rolling direction of the steel sheet, and reducing impurities in the steel sheet. Techniques developed to improve eddy current loss include increasing the electrical resistance of the steel sheet by adding Si, and applying coating tension in the rolling direction of the steel sheet. However, these techniques have limitations in the manufacture of grain-oriented electrical steel sheets.
[0004] Therefore, to further reduce the iron loss of grain-oriented electrical steel sheets, magnetic domain refinement technology has been developed. Magnetic domain refinement technology is a technology that reduces the iron loss, especially the eddy current loss, of grain-oriented electrical steel sheets in the following manner. That is, after finish annealing (hereinafter also referred to as final annealing) or after baking of the insulating coating, non-uniformity of magnetic flux is introduced into the steel sheet by physical means such as forming grooves or introducing localized distortion. This refines the width of the 180° magnetic domains (main magnetic domains) formed along the rolling direction of the steel sheet, reducing the iron loss, especially the eddy current loss, of the grain-oriented electrical steel sheet.
[0005] For example, Patent Document 1 states: "A wound core for a transformer with low iron loss, characterized in that the wound core is made by winding and overlapping grain-oriented electromagnetic steel sheets on one surface of which linear grooves are formed with a groove width of 300 μm or less, a groove depth of 100 μm or less, a groove center line spacing of 1 mm or more in the rolling direction, and an angle of 30° or more with the rolling direction, the linear grooves facing the inward winding side, and the radius of curvature of the innermost bent portion is 30 mm or less." has been disclosed. The technique of forming grooves on the surface of a steel sheet to subdivide magnetic domains as described in Patent Document 1 is also called a heat-resistant magnetic domain refinement technique because the magnetic domain refinement effect does not disappear even when stress relief annealing is performed. Here, stress relief annealing is a heat treatment for releasing strain that is inevitably introduced into the grain-oriented magnetic steel sheet, for example, by bending the grain-oriented magnetic steel sheet to make it into a wound core. Note that this strain is different from the strain introduced by the magnetic domain refinement treatment and has an adverse effect on iron loss.
[0006] In addition, Patent Document 2 states: "A method for manufacturing low-iron-loss grain-oriented silicon steel sheet, characterized in that a highly convergent sheet-shaped plasma flame is emitted onto the surface of grain-oriented silicon steel sheet that has been subjected to final annealing to subdivide magnetic domains." has been disclosed. The technique of refining magnetic domains by introducing thermal strain into a steel sheet as described in Patent Document 2 is also called a non-heat-resistant magnetic domain refinement technique because the magnetic domain refinement effect disappears due to strain relief annealing.
[0007] Furthermore, as a technique for forming grooves on the surface of the above-mentioned steel sheet to subdivide magnetic domains (heat-resistant magnetic domain subdivision technique), Patent Document 3 proposes an electrolytic etching method in which grooves are formed on the surface of the steel sheet by electrolytic etching. Patent Document 4 proposes a laser method in which a high-power laser is used to locally melt and evaporate the steel sheet. Patent Document 5 proposes a gear press method in which a roll on a gear is pressed against a steel sheet to give an indentation. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 6-022179 [Patent Document 2] Japanese Patent Application Publication No. 7-192891 [Patent Document 3] JP 2012-77380 A [Patent Document 4] JP 2003-129135 A [Patent Document 5] Japanese Patent Application Publication No. 62-086121 Summary of the Invention [Problem to be solved by the invention]
[0009] In recent years, from the viewpoint of energy conservation and environmental regulations, there has been a demand to reduce the noise generated during operation of transformers in addition to reducing their energy loss. The noise generated during operation of transformers is affected by the magnetostrictive properties of grain-oriented electrical steel sheets. Therefore, it has become extremely important to develop grain-oriented electrical steel sheets that combine low iron loss with good magnetostrictive properties.
[0010] Among the above-mentioned magnetic domain refinement techniques, the non-heat-resistant magnetic domain refinement technique described in Patent Document 2 can significantly reduce eddy current loss by introducing local strain into the steel sheet. However, on the other hand, the non-heat-resistant magnetic domain refinement leads to an increase in hysteresis loss and deterioration of magnetostriction characteristics due to the introduction of such strain. Also, as described above, in grain-oriented electrical steel sheet that has been subjected to the non-heat-resistant magnetic domain refinement technique, the magnetic domain refinement effect disappears due to strain relief annealing, so its applications are limited.
[0011] On the other hand, in the heat-resistant magnetic domain refinement technology as disclosed in Patent Documents 1, 3 to 5, the effect is greater as the area of the groove portion in the rolling direction cross section of the steel sheet becomes larger. However, forming the groove deep in the thickness direction of the steel sheet leads to deterioration of the magnetic properties of the steel sheet, such as a decrease in magnetic permeability. In addition, manufacturing disadvantages such as breakage of the steel sheet also occur. Thus, in the heat-resistant magnetic domain refinement technology, the depth of the groove in the steel sheet is limited, and therefore, there is a current demand for further reduction in iron loss while maintaining high magnetic permeability.
[0012] The present invention has been developed in view of the above-mentioned current situation, and has an object to provide a grain-oriented electrical steel sheet having low core loss, high magnetic permeability and good magnetostriction characteristics. [Means for solving the problem]
[0013] As a result of extensive research into achieving the above object, the inventors have come to the following findings. (a) In magnetic domain refinement technology, magnetic poles are formed at the boundaries of regions with different magnetic permeability in the rolling direction. The width of the main magnetic domain of the steel sheet is refined to reduce the increased magnetostatic energy caused by these magnetic poles. (b) In the heat-resistant magnetic domain refinement technology, the gaps in the grooves are used as areas of different magnetic permeability. These gaps do not change even when stress relief annealing is performed, so the magnetic domain refinement effect is maintained. However, the gaps in the grooves reduce the magnetic permeability of the entire steel sheet. (c) On the other hand, in the non-heat-resistant magnetic domain refinement technology, thermal distortion is introduced into the steel sheet by irradiating it with an energy beam. The residual stress generated by this thermal distortion forms new magnetic domains (closure domains) with magnetization components in the crystal's
[0010] or
[0100] orientation (when the crystal's
[0001] orientation is the rolling direction). Here, the crystal's
[0010] or
[0100] orientation corresponds to the direction between the sheet's width direction and thickness direction (45° from the sheet's width direction to the sheet's thickness direction), respectively. Since the magnetization directions of the main magnetic domain and the closure domain are different, a change in magnetic permeability occurs in the rolling direction, and magnetic domain refinement occurs. This thermal distortion is eliminated by stress relief annealing, and the magnetic domain refinement effect also disappears by stress relief annealing. However, since both the main magnetic domain and the closure domain are formed inside the grain-oriented electrical steel sheet, the magnetic permeability of the steel sheet as a whole hardly changes.
[0014] Therefore, the inventors thought that if it were possible to form closure domains in a heat-resistant magnetic domain refinement technology that would maintain residual stress inside the steel sheet even after stress relief annealing, it might be possible to obtain an extremely high iron loss reduction effect and suppress a decrease in magnetic permeability, even without forming grooves deep in the thickness direction of the steel sheet.
[0015] Based on the above idea, the inventors conducted further research and discovered that by locally melting and solidifying the steel plate using an energy beam to form a linear molten solidified portion that crosses the rolling direction on one surface of the steel plate, residual stress can be maintained inside the steel plate even after stress relief annealing.
[0016] The inventors also formed linear molten solidified portions crossing the rolling direction on one surface of a grain-oriented electrical steel sheet under various conditions. As a result, the inventors found that, in the distribution of anisotropic energy from the surface of the molten and solidified part in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction, ΔE (KJ / m 3 It has been found that by making the deepest position of the region where the θ is negative 4 μm or more from the surface of the molten solidified portion, a high iron loss improvement effect can be obtained while ensuring high magnetic permeability and good magnetostriction characteristics for the steel sheet as a whole, even when subjected to strain relief annealing. Here, ΔE is defined by the following formula (1). ΔE=E sub -E RD (1) In formula (1), E RD (KJ / m 3 ) and E sub (KJ / m 3 ) are the anisotropy energy in the rolling direction, and the anisotropy energy in the crystal's <0010> orientation or <0100> orientation when the crystal's <0001> orientation is the rolling direction, respectively, and are calculated using the following equations (2) to (4).
number
number
number
[0017] Furthermore, the inventors have conducted further studies and found that even better effects can be obtained by further satisfying the following points. In the distribution of anisotropic energy from the surface of the molten and solidified part in the rolling direction cross section of grain-oriented electrical steel sheet to the sheet thickness direction, ΔE (KJ / m 3 ) is -2KJ / m 3 The deepest position of the region below is set to a distance of 4 μm to 40 μm from the surface of the molten solidified portion. A groove defined by a molten and solidified portion is formed on one surface of the grain-oriented electrical steel sheet. In the depth profile of the groove (cross-sectional shape of the groove) as shown in Figure 1, the depth d of the deepest point of the groove is less than 8.0 μm. In the depth profile of the above groove, at least two minimum values are provided, and the ratio of the depth d of the deepest point of the groove to the width W of the groove, d / W×100(%), is set to be 5% or more and less than 20%. The distance between the molten and solidified portions in the rolling direction must be 1.0 mm or more and less than 5.0 mm. The present invention was completed based on the above findings and through further investigation.
[0018] That is, the gist and configuration of the present invention are as follows. 1. Grain-oriented electrical steel sheet, The grain-oriented electrical steel sheet has, on one surface thereof, periodically linear molten and solidified portions that cross the rolling direction, In the distribution of anisotropic energy from the surface of the molten solidified portion in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction, ΔE (KJ / m 3 ) is negative, the deepest position of which is 4 μm or more away from the surface of the molten solidified portion. Here, ΔE is defined by the following formula (1). ΔE=E sub -E RD (1) In formula (1), E RD (KJ / m 3 ) and E sub (KJ / m 3 ) are the anisotropy energy in the rolling direction, and the anisotropy energy in the crystal's <0010> orientation or <0100> orientation when the crystal's <0001> orientation is the rolling direction, respectively, and are calculated using the following equations (2) to (4).
number
number
number
[0019] 2. In the distribution of anisotropic energy, the ΔE (KJ / m 3 ) is -2KJ / m 3 2. The grain-oriented electrical steel sheet according to 1, wherein the deepest position of the region where:
[0020] 3. The grain-oriented electrical steel sheet according to 1 or 2 above, having a groove portion defined by the molten solidified portion.
[0021] 4. The grain-oriented electrical steel sheet according to 3, wherein in a depth profile of the groove, the depth d of the deepest point of the groove is less than 8.0 μm.
[0022] 5. In the depth profile of the groove, there are two or more minimum values; 5. The grain-oriented electrical steel sheet according to 3 or 4, wherein the ratio of the depth d of the deepest point of the groove to the width W of the groove, d / W×100(%), is 5% or more and less than 20%.
[0023] 6. The grain-oriented electrical steel sheet according to any one of 1 to 5 above, wherein the interval between the molten solidified portions in the rolling direction is 1.0 mm or more and less than 5.0 mm. Effect of the Invention
[0024] According to the present invention, it is possible to obtain a grain-oriented electrical steel sheet having low iron loss, high magnetic permeability and good magnetostriction characteristics. Furthermore, since the grain-oriented electrical steel sheet of the present invention has low iron loss even after stress relief annealing, high magnetic permeability and good magnetostriction characteristics, it can be used extremely advantageously as an iron core material for transformers, particularly wound core transformers, etc. [Brief description of the drawings]
[0025] [Figure 1]FIG. 2 is a schematic diagram showing an example of a depth profile of a groove (cross-sectional shape of a groove). [Diagram 2] FIG. 13 is a schematic diagram showing an example of anisotropic energy distribution. [Diagram 3] FIG. 13 is a diagram showing the relationship between the deepest position where ΔE<0 is located and iron loss W17 / 50. [Figure 4] FIG. 4 is an enlarged view of a portion of FIG. [Diagram 5] FIG. 13 is a diagram showing the relationship between the deepest position where ΔE≦−2 is satisfied and iron loss W17 / 50. [Figure 6] FIG. 6 is an enlarged view of a portion of FIG. 5. [Figure 7] FIG. 13 is a diagram showing the relationship between the deepest position where ΔE<0 is reached and magnetostrictive harmonics MHL15 / 50. [Figure 8] FIG. 13 is a diagram showing the relationship between the deepest position of ΔE≦−2 and magnetostrictive harmonics MHL15 / 50. [Figure 9] FIG. 13 is a diagram showing the relationship between the deepest position of ΔE<0 and ΔB8. [Figure 10] FIG. 13 is a diagram showing the relationship between the deepest position of ΔE≦−2 and ΔB8. [Figure 11] FIG. 11 is a diagram showing the relationship between the depth d of the deepest point of the groove and iron loss W17 / 50. [Figure 12] FIG. 13 is a diagram showing the relationship between the depth d of the deepest point of a groove and magnetostrictive harmonics MHL15 / 50. [Figure 13] FIG. 13 is a diagram showing the relationship between the depth d of the deepest point of a groove portion and ΔB8. [Figure 14] FIG. 1 is a diagram showing the relationship between d / W×100 and iron loss W17 / 50. [Figure 15] FIG. 13 is a diagram showing the relationship between d / W×100 and magnetostrictive harmonics MHL15 / 50. [Figure 16] FIG. 13 is a graph showing the relationship between d / W×100 and ΔB8. [Figure 17] FIG. 1 is a diagram showing the relationship between the interval between molten and solidified portions and iron loss W17 / 50. [Figure 18] FIG. 13 is a diagram showing the relationship between the interval between the molten and solidified portions and the magnetostrictive harmonic MHL15 / 50. [Figure 19]FIG. 13 is a graph showing the relationship between the interval between molten and solidified portions and ΔB8. [Figure 20] FIG. 4 is a schematic diagram showing a method for measuring a width W of a groove. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] First, the experimental results that led to the completion of the present invention will be described. (Experiment 1) Several samples of the same shape were cut out from grain-oriented electrical steel sheets (steel strips) manufactured by a general manufacturing process, and the magnetic properties, specifically B8 and W, were measured by the Epstein method described in JIS C2550. 17 / 50 The B8 and W 17 / 50 The measured values were 1.9350 T and 0.880 W / kg, respectively. Here, B8 means the magnetic flux density when magnetized in the rolling direction with a magnetizing force of 800 A / m. W 17 / 50 The iron loss value is the value when an alternating magnetization of 1.7 T and 50 Hz is applied in the rolling direction. Next, for each sample, a laser output density of 0.1 to 1.0 (J / mm 2 ), the sample was locally melted and solidified, forming a linear melted and solidified part on the surface of the sample. The laser power density is expressed as P / (v Φ), where v is the scanning speed (hereinafter also referred to as the deflection speed), Φ is the spot diameter in the direction perpendicular to the scanning direction, and P is the laser power. A single-mode fiber laser was used as the laser source, and no assist gas was used. The laser was irradiated at intervals of 4.0 mm in the rolling direction.
[0027] After the laser irradiation, each sample was subjected to stress relief annealing at 800°C for 3 hours in a nitrogen atmosphere. Then, each sample was subjected to the Epstein method according to JIS C2550 to obtain B8 and W. 17 / 50 In addition, for each sample, ΔB8 (=[B8 measured on the sample after laser irradiation (hereinafter also referred to as the post-irradiation sample)] - [B8 measured on the sample before laser irradiation (hereinafter also referred to as the pre-irradiation sample)]) was calculated as an index of the change in magnetic permeability.
[0028] Next, the magnetostrictive vibration waveform of each post-irradiation sample was measured using a laser Doppler magnetostrictive vibrometer when it was magnetized with a 1.5T, 50Hz sinusoidal AC current. The measured magnetostrictive vibration waveform was then Fourier-decomposed into vibration acceleration components with frequencies of every 100Hz. Next, the values of each frequency component, which were weighted for hearing on the A scale, were integrated from 0 to 1000Hz, and the integrated values were used as magnetostrictive harmonics MHL, which are an index of magnetostrictive properties. 15 / 50 It was decided.
[0029] Next, each post-irradiation sample was embedded in a mold and mirror-polished, and then the strain distribution in the rolling direction cross section of the sample was obtained by the EBSD Wilkinson method. Then, from the obtained strain distribution, ΔE was calculated using the above formulas (1) to (4), and the distribution of anisotropic energy from the surface of the molten solidified part in the rolling direction cross section of the sample to the sheet thickness direction was obtained. For reference, FIG. 2 shows a schematic diagram of an example of the distribution of the anisotropic energy. Note that the grain-oriented electrical steel sheet having the anisotropic energy distribution illustrated in FIG. 2 does not have a groove portion defined by the molten solidified part, that is, the surface of the grain-oriented electrical steel sheet is flat.
[0030] From the distribution of anisotropy energy of each sample thus obtained, ΔE (KJ / m 3 ) is negative (hereinafter referred to as the deepest position of ΔE<0) and ΔE(KJ / m 3 ) is -2KJ / m 3 The deepest position of the region where ΔE≦−2 (hereinafter also referred to as the deepest position where ΔE≦−2) was determined.
[0031] 3 to 10 show the above measurement results plotted against the deepest position where ΔE<0 and the deepest position where ΔE≦-2. Here, Fig. 3 shows the relationship between the deepest position of ΔE<0 and the iron loss W (of the irradiated sample). 17 / 50 FIG. 4 shows the relationship between the above and FIG. 3, and is an enlarged view of a portion of FIG. Figure 5 shows the deepest position of ΔE≦-2 and the iron loss W (of the irradiated sample) 17 / 50 FIG. 6 shows a part of FIG. 5 in an enlarged scale. Figure 7 shows the deepest position of ΔE<0 and magnetostrictive harmonic MHL. 15 / 50 This shows the relationship between Figure 8 shows the deepest position of ΔE≦-2 and magnetostriction harmonic MHL. 15 / 50 This shows the relationship between FIG. 9 shows the relationship between the deepest position where ΔE<0 is satisfied and ΔB8. FIG. 10 shows the relationship between the deepest position for ΔE≦−2 and ΔB8.
[0032] 3 and 4, it can be seen that a high iron loss improvement effect can be obtained when the deepest position of ΔE<0 is 4 μm or more. It can also be seen that a particularly high iron loss improvement effect can be obtained when the deepest position of ΔE<0 is 6 μm or more. The inventors believe that the reason for this is that even after stress relief annealing, stress remains inside the steel sheet due to the presence of the molten solidified part, and closure domains are generated. On the other hand, when the deepest position of ΔE<0 is less than 4 μm (including when the deepest position of ΔE<0 is 0 μm, i.e., when ΔE is all positive), a sufficient iron loss improvement effect cannot be obtained. The inventors believe that the reason for this is that closure domains are not generated sufficiently.
[0033] 5 and 6 show that a particularly high iron loss improvement effect is obtained when the deepest position of ΔE≦-2 is 4 μm or more. The inventors believe that the reason for this is that the magnetic anisotropy of the closure domains increases, allowing the closure domains to exist up to high magnetic fields during excitation, resulting in a higher magnetic domain refinement effect.
[0034] As shown in Fig. 7, as the deepest position of ΔE<0 increases, the magnetostrictive harmonic MHL 15 / 50 It can be seen that there is a tendency for the magnetostrictive harmonic MHL to increase. The inventors believe that the reason for this is that the creation and disappearance of closure domains occurs during the AC magnetization process, making the magnetostrictive vibration more complex. In particular, when the deepest position of ΔE<0 becomes 120 μm, the magnetostrictive harmonic MHL 15 / 50 Therefore, the deepest position where ΔE<0 is preferably 100 μm or less, more preferably 50 μm or less.
[0035] As can be seen from Fig. 8, as with the deepest position of ΔE<0, the magnetostrictive harmonic MHL 15 / 50 Therefore, the deepest position where ΔE≦-2 is preferably 80 μm or less, and more preferably 40 μm or less.
[0036] 9 and 10, even when the deepest position of ΔE<0 and the deepest position of ΔE≦-2 are deeper, ΔB8 is less than -0.0010 T, and almost no deterioration in magnetic permeability is observed. The inventors believe that the reason for this is that the melted and solidified portion grows epitaxially from the surrounding GOSS-oriented grains, so that the melted and solidified portion also maintains the GOSS orientation.
[0037] From the above results, in order to achieve low iron loss, low magnetostriction, and high magnetic permeability even after stress relief annealing, it is necessary to set the deepest position where ΔE<0 to 4 μm or more. It is also preferable to set the deepest position where ΔE<0 to 6 μm or more. Furthermore, it is preferable to set the deepest position where ΔE<0 to 100 μm or less, and more preferably to set it to 50 μm or less. Furthermore, in order to obtain a higher effect, it is preferable that the deepest position of ΔE≦−2 is 4 μm or more and 80 μm or less, and it is more preferable that it is 4 μm or more and 40 μm or less.
[0038] (Experiment 2) Several samples of the same shape were cut out from grain-oriented electrical steel sheets (steel strips) manufactured by a general manufacturing process, and were then subjected to the Epstein method described in JIS C2550 to determine the B8 and W 17 / 50 The B8 and W 17 / 50The measured values of were 1.9350 T and 0.880 W / kg, respectively. Next, an electron beam was irradiated across the rolling direction for each sample, and the sample was locally melted and solidified to form linear melted solidified areas and grooves defined by the melted solidified areas on the surface of the sample. The power density of the electron beam was adjusted so that the deepest position where ΔE≦-2 was 15 μm. The power density of the electron beam is expressed as P / (v Φ) using the deflection speed v, the spot diameter Φ in the direction perpendicular to the scanning direction, and the electron beam output P. A thermionic electron gun with a LaB6 chip as the cathode was used as the electron gun. The electron beam was irradiated at intervals of 4.0 mm in the rolling direction. In addition, the shape of the electron beam spot was shaped as an ellipse with the major axis in the scanning direction using a focusing coil, and the ellipticity was changed variously in the range of 1.1 to 12 for each sample.
[0039] After the electron beam irradiation, each sample was subjected to stress relief annealing at 800°C for 3 hours in a nitrogen atmosphere. Then, each sample was subjected to the Epstein method according to JIS C2550 to obtain B8 and W. 17 / 50 was measured. In addition, for each sample, ΔB8 (= [B8 measured for the sample after laser irradiation (hereinafter also referred to as the post-irradiation sample)] - [B8 measured for the sample before laser irradiation (hereinafter also referred to as the pre-irradiation sample)]) was calculated as an index of the change in magnetic permeability. In addition, in the same manner as in Experiment 1, the magnetostrictive harmonic MHL, which is an index of the magnetostrictive properties, was calculated for each post-irradiation sample. 15 / 50 asked for.
[0040] Next, for each irradiated sample, a depth profile of the groove was created from the surface using a laser microscope, and the depth d of the deepest point of the groove (the distance in the sheet thickness direction between the deepest point of the groove and the surface of the grain-oriented electrical steel sheet) was measured.
[0041] 11 to 13 show the above measurement results plotted against the depth d of the deepest point of the groove portion. Here, Fig. 11 shows the relationship between the depth d of the deepest point of the groove and the iron loss W (of the irradiated sample). 17 / 50 This shows the relationship between Figure 12 shows the relationship between the depth d of the deepest point of the groove and the magnetostrictive harmonic MHL. 15 / 50This shows the relationship between FIG. 13 shows the relationship between the depth d of the deepest point of the groove and ΔB8.
[0042] 11, the greater the depth d of the deepest point of the groove, that is, the deeper the groove, the greater the tendency for iron loss to be improved. In particular, it can be seen that a high iron loss improvement effect can be obtained when the depth d of the deepest point of the groove is 1.0 μm or more. The inventors believe that the reason for this is that the free magnetic pole formed on the wall surface around the deepest point of the groove promotes magnetic domain refinement.
[0043] From Fig. 12, magnetostrictive harmonics MHL 15 / 50 It can be seen that is hardly affected by the depth d of the deepest point of the groove.
[0044] 13, ΔB8, which is an index of change in magnetic permeability, tends to increase as the depth d of the deepest point of the groove increases, that is, as the groove becomes deeper. In particular, when the depth d of the deepest point of the groove exceeds 8.0 μm, ΔB8 tends to increase significantly. The inventors believe that the reason for this is that the groove becomes deeper, increasing the volume of the groove, which is a void, and thus deteriorating the magnetic permeability.
[0045] From the above results, in order to achieve low iron loss, low magnetostriction, and high magnetic permeability even after stress relief annealing, the depth d of the deepest point of the groove is preferably less than 8.0 μm. More preferably, the depth d of the deepest point of the groove is less than 7.0 μm. Moreover, the depth d of the deepest point of the groove is more preferably 1.0 μm or more.
[0046] (Experiment 3) Several samples of the same shape were cut out from grain-oriented electrical steel sheets (steel strips) manufactured by a general manufacturing process, and were then subjected to the Epstein method described in JIS C2550 to determine the B8 and W 17 / 50 The B8 and W 17 / 50The measured values of were 1.9350 T and 0.880 W / kg, respectively. Next, a laser was irradiated across the rolling direction for each sample, and the sample was locally melted and solidified to form linear melted solidified parts and grooves defined by the melted solidified parts on the surface of the sample. The power density of the laser was adjusted so that the deepest position of ΔE≦-2 was 15 μm. The power density of the laser is expressed as P / (v Φ) using the deflection speed v, the spot diameter Φ in the direction perpendicular to the scanning direction, and the laser output P. A single-mode fiber laser was used as the laser source, and no assist gas was used. The laser was irradiated at intervals of 4.0 mm in the rolling direction. In addition, a cylindrical lens was used to make the shape of the laser spot an ellipse with the major axis in the scanning direction, and the ellipticity was changed variously in the range of 1.1 to 12 for each sample.
[0047] After the laser irradiation, each sample was subjected to stress relief annealing at 800°C for 3 hours in a nitrogen atmosphere. Then, each sample was subjected to the Epstein method according to JIS C2550 to obtain B8 and W. 17 / 50 was measured. In addition, for each sample, ΔB8 (= [B8 measured for the sample after laser irradiation (hereinafter also referred to as the post-irradiation sample)] - [B8 measured for the sample before laser irradiation (hereinafter also referred to as the pre-irradiation sample)]) was calculated as an index of the change in magnetic permeability. In addition, in the same manner as in Experiment 1, the magnetostrictive harmonic MHL, which is an index of the magnetostrictive properties, was calculated for each post-irradiation sample. 15 / 50 asked for.
[0048] Next, for each post-irradiation sample, a depth profile of the groove was created from its surface using a laser microscope, and the groove width W, the depth d of the deepest point of the groove, and the number of minimum values N were measured. The number of maximum values is N-1. If there are no grooves, that is, if the surface of the steel plate is flat, the number of minimum values and maximum values in the groove will both be 0. The method for measuring the depth profile of the groove will be described later.
[0049] 14 to 16 show the above measurement results, plotted against d / W×100(%) for each number N of minimum values. Here, Fig. 14 shows the relationship between d / W×100 and the iron loss (of the irradiated sample) W 17 / 50 This shows the relationship between Figure 15 shows the relationship between d / W×100 and magnetostriction harmonics MHL. 15 / 50 This shows the relationship between FIG. 16 shows the relationship between d / W×100 and ΔB8.
[0050] As shown in FIG. 14, when d / W×100 is 5% or more, a high iron loss improvement effect tends to be obtained. The inventors believe that the reason for this is that the inclination of the groove defined by the molten solidified portion approaches vertical, or the groove is formed deep, so that the magnetic poles generated on the wall surface increase. It can also be seen that the higher the number of minimum values N, especially when it is 2 or more, the higher the iron loss improvement effect can be obtained. The inventors believe that the reason for this is that the shape of the molten solidified portion becomes more complex, so that larger stress remains inside the steel sheet, making it possible to maintain the closure domain up to a higher magnetic field.
[0051] From Fig. 15, when d / W×100 is 20% or more, magnetostrictive harmonics MHL 15 / 50 In particular, this tendency becomes more pronounced as the number N of minimum values increases. The inventors believe that the reason for this is that as the shape of the molten solidified portion becomes more complex, a larger stress remains inside the steel sheet, and more closure domains are generated.
[0052] It can be seen from FIG. 16 that ΔB8, which is an index of permeability change, is hardly affected by d / W×100 and the number N of minimum values.
[0053] From the above results, in order to achieve low core loss, low magnetostriction, and high magnetic permeability even after stress relief annealing, it is preferable that d / W×100 is 5% or more and less than 20%, and the number N of minimum values is 2 or more. d / W×100 is more preferably 7% or more. d / W×100 is more preferably 18% or less.
[0054] (Experiment 4) Several samples of the same shape were cut out from grain-oriented electrical steel sheets (steel strips) manufactured by a general manufacturing process, and were then subjected to the Epstein method described in JIS C2550 to determine the B8 and W 17 / 50 The B8 and W 17 / 50 The measured values of were 1.9350 T and 0.880 W / kg, respectively. Next, a laser was irradiated across the rolling direction for each sample, and the sample was locally melted and solidified to form linear melted solidified areas and grooves defined by the melted solidified areas on the surface of the sample. The power density of the laser was adjusted so that the deepest position of ΔE≦-2 was 20 μm, the number of minimum values N in the depth profile of the grooves was two, and d / W×100 was 10%. The power density of the laser was expressed as P / (v Φ) using the deflection speed v, the spot diameter Φ in the direction perpendicular to the scanning direction, and the laser power P. A single-mode fiber laser was used as the laser source, and no assist gas was used. The interval of the laser irradiation in the rolling direction was changed variously in the range of 0.5 to 7.0 mm for each sample. In addition, a diffractive optical element was used to set the shape of the laser spot to a line segment shape in which the scanning direction was the stretching direction, and irradiation was performed while changing Ll / Lw, which is the ratio of the line segment length Ll to the spot width Lw in the rolling direction, in the range of 1.1 to 6.
[0055] After the laser irradiation, each sample was subjected to stress relief annealing at 800°C for 3 hours in a nitrogen atmosphere. Then, each sample was subjected to the Epstein method according to JIS C2550 to obtain B8 and W. 17 / 50 was measured. In addition, for each sample, ΔB8 (= [B8 measured for the sample after laser irradiation (hereinafter also referred to as the post-irradiation sample)] - [B8 measured for the sample before laser irradiation (hereinafter also referred to as the pre-irradiation sample)]) was calculated as an index of the change in magnetic permeability. In addition, in the same manner as in Experiment 1, the magnetostrictive harmonic MHL, which is an index of the magnetostrictive properties, was calculated for each post-irradiation sample. 15 / 50 asked for.
[0056] 17 to 19 show the above measurement results plotted against the interval of laser irradiation in the rolling direction, that is, the interval of the molten solidified portions in the rolling direction (hereinafter also referred to as the interval of the molten solidified portions). Here, Fig. 17 shows the relationship between the interval of the molten solidified part and the iron loss (of the irradiated sample) W 17 / 50 This shows the relationship between Figure 18 shows the relationship between the distance between the molten and solidified parts and the magnetostrictive harmonic wave (MHL). 15 / 50 This shows the relationship between FIG. 19 shows the relationship between the distance between the molten and solidified portions and ΔB8.
[0057] 17, there is a tendency that the smaller the interval between the molten and solidified parts, the greater the iron loss improvement effect. The inventors believe that the reason for this is that the smaller the interval between the molten and solidified parts, the larger the area of the molten and solidified parts, and therefore the interface area between the closure domain and the main domain, and the total amount of magnetic poles increases.
[0058] As can be seen from Fig. 18, the smaller the gap between the molten and solidified parts, the greater the magnetostrictive harmonic MHL. 15 / 50 The inventors believe that the reason for this is that the magnetostrictive vibration becomes more complicated as the total number of closure domains increases.
[0059] From FIG. 19, it can be seen that ΔB8, which is an index of change in magnetic permeability, is hardly affected by the interval between the molten and solidified portions.
[0060] From the above results, in order to realize high low iron loss, low magnetostriction, and high magnetic permeability even after stress relief annealing, it is preferable that the interval between the molten solidified parts is 1.0 mm or more and less than 5.0 mm. The interval between the molten solidified parts is more preferably 2.0 mm or more. The interval between the molten solidified parts is more preferably 4.0 mm or less.
[0061] Next, a grain-oriented electrical steel sheet according to an embodiment of the present invention, which has been completed based on the above experimental results, will be described. The grain-oriented electrical steel sheet according to one embodiment of the present invention has linear molten solidified portions periodically crossing the rolling direction on one surface thereof, In the distribution of anisotropic energy from the surface of the molten solidified portion in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction, ΔE (KJ / m 3) is negative, the deepest position of which is 4 μm or more away from the surface of the molten solidified portion. Here, ΔE is defined by the following formula (1). ΔE=E sub -E RD (1) In formula (1), E RD (KJ / m 3 ) and E sub (KJ / m 3 ) are the anisotropy energy in the rolling direction, and the anisotropy energy in the crystal's <0010> orientation or <0100> orientation when the crystal's <0001> orientation is the rolling direction, respectively, and are calculated using the following equations (2) to (4).
number
number
number
[0062] First, it is important that the grain-oriented electrical steel sheet according to one embodiment of the present invention has a linear molten solidified portion on one surface thereof that crosses the rolling direction. Here, the molten solidified portion is a region in which the base material of the grain-oriented electrical steel sheet is melted by heat, and then cooled and solidified. In addition, a heat-affected zone is usually formed adjacent to the molten solidified portion. The molten solidified portion is defined as follows. That is, the grain-oriented electrical steel sheet is cut so that the cross section in the rolling direction of the grain-oriented electrical steel sheet becomes the cut surface. Next, the cut surface is subjected to distortion-free polishing. Next, the crystal orientation difference of the polished surface is analyzed by EBSD (Electron Backscatter Diffraction) and the KAM (Karnel Average Misorientation) value is measured. The area with a KAM value of 3.0° or more is the molten and solidified area, the area with residual elastic strain in the strain distribution analyzed by the EBSD Wilkinson method described below and with a KAM value of less than 3.0° is the heat-affected area, and the other areas (areas with no residual elastic strain and with a KAM value of less than 3.0°) are the base material area.
[0063] In the non-heat-resistant magnetic domain refinement technique described in Patent Document 2, the thermal strain introduced into the steel sheet by non-heat-resistant magnetic domain refinement, and hence the residual stress inside the steel sheet due to the thermal strain, are released by stress relief annealing. In contrast, in the grain-oriented electrical steel sheet according to one embodiment of the present invention, the residual stress inside the steel sheet caused by the molten and solidified portion is maintained even when stress relief annealing is performed. The inventors consider the reason for this to be as follows. That is, when a steel plate is locally heated and melted, it is rapidly cooled from the molten metal state and solidified. It is presumed that this process causes solidification to be completed before the distortion caused by the phase transformation of the molten part is fully eliminated. In particular, it is believed that such residual distortion becomes large because the molten solidified part has a complex shape with multiple minimum values in the depth profile of the groove part defined by the molten solidified part.
[0064] In a grain-oriented electrical steel sheet according to one embodiment of the present invention, the deepest position where ΔE<0 is a distance (in the sheet thickness direction) from the surface of the molten solidified portion is 4 μm or more; in other words, it is necessary that the region where ΔE is negative extends to a depth of 4 μm or more from the surface of the molten solidified portion.
[0065] Deepest position of ΔE<0: Distance from the surface of the molten solidified part is 4μm or more From the above experimental results, it is necessary that the deepest position of ΔE<0 is 4 μm or more from the surface of the molten solidified portion. The preferable range of the deepest position of ΔE<0 is as shown in the above experimental results.
[0066] The preferable range of the deepest position where ΔE≦-2 is also as shown in the above-mentioned experimental results. The deepest position where ΔE≦-2 is most preferably a distance (in the plate thickness direction) of 4 μm to 40 μm from the surface of the molten solidified portion.
[0067] Here, the deepest position where ΔE<0 and the deepest position where ΔE≦-2 are obtained from the distribution of anisotropic energy from the surface of the molten solidified part in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction. The anisotropic energy at each position in the distribution of anisotropic energy is basically calculated at a pitch of 1 μm. However, in areas where a certain tendency can be grasped, the anisotropic energy may be calculated at a larger pitch, for example, a pitch of 5 to 10 μm.
[0068] For example, in the distribution of anisotropic energy, if ΔE from the surface of the molten solidified part to a depth of 10 μm is negative and ΔE at a depth of 11 μm is positive, the deepest position where ΔE<0 is 10 μm. Similarly, if ΔE from the surface of the molten solidified part to a depth of 10 μm is -2 KJ / m 3 Below, ΔE at a depth of 11 μm is -1 KJ / m 3 In this case, the deepest position for ΔE≦−2 is 10 μm.
[0069] In addition, the distribution of anisotropic energy from the surface of the molten solidified part in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction (ΔE at various depth positions) is shown in Fig. 1. The distribution of strain from the surface of the molten solidified part in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction (ε RD , ε TD and ε ND ) using the above formulas (1) to (4). In addition, the strain distribution from the surface of the molten solidified part in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction (ε RD , ε TD and ε ND ) is obtained by the EBSD Wilkinson method. In the EBSD Wilkinson method, an electron beam is irradiated onto the rolling direction cross section of the grain-oriented electrical steel sheet, and a Kikuchi pattern is obtained for each measurement point. Then, using the no-strain point as a reference point, an analysis software such as CrossCourt is used to calculate the amount of strain from the deformation amount of the Kikuchi pattern at each measurement point. If a groove defined by the molten solidified portion exists, the strain distribution from the deepest point of the groove in the rolling direction cross section to the plate thickness direction may be measured, and the distribution of anisotropic energy may be created. If no groove exists (the steel sheet surface is flat), the strain distribution from the width center of the surface of the molten solidified portion in the rolling direction cross section to the plate thickness direction may be measured, and the distribution of anisotropic energy may be created.
[0070] Moreover, the grain-oriented electrical steel sheet according to an embodiment of the present invention preferably has a groove defined by the above-mentioned molten solidified portion. Even when there are two minimum values in the depth profile of the groove as shown in Fig. 1, the groove is considered to be one groove if the groove is defined by one molten solidified portion (the wall surface, bottom (valley portion) and peak portion of the groove are composed of one molten solidified portion).
[0071] Here, the shape of the groove is preferably such that the depth d of the deepest point of the groove is less than 8 μm in the depth profile of the groove. The reason is as shown in the above-mentioned experimental results. Moreover, the more preferable range of the depth d of the deepest point of the groove is also as shown in the above-mentioned experimental results.
[0072] It is also preferable that the depth profile of the groove has two or more minimum values, and the ratio of the depth d of the deepest point of the groove to the width W of the groove, d / W×100(%), is 5% or more and less than 20%. The reason for this is as shown in the experimental results described above. The more preferable ranges for the number N of minimum values and d / W×100(%) are also as shown in the experimental results described above.
[0073] Here, the depth profile of the groove is created as follows. That is, the surface of the grain-oriented electrical steel sheet is observed using a laser microscope, and the depth of the groove is continuously measured at 1 μm intervals along the direction perpendicular to the extension direction of the molten solidified part. Then, in the sheet thickness direction, the side where the groove (molten solidified part) exists is set as +, the opposite side is set as -, and the steel sheet surface level is set as 0. The measured depth of the groove is smoothed (smoothed) by a three-point moving average method and then plotted to create a depth profile of the groove. Then, from the created depth profile of the groove, the points that take the minimum and maximum values are determined, and the number of points that take the minimum and maximum values is obtained. In addition, the distance from the steel sheet surface to the point that takes the minimum value in the depth profile of the groove is set as the depth d of the deepest point of the groove.
[0074] In addition, the width W of the groove is measured as the distance between the ends of the groove in the extending vertical direction of the molten solidified portion at the position level of the steel plate surface, as shown in Fig. 20. Note that Fig. 20 is a schematic diagram showing an example of the cross-sectional shape of the molten solidified portion (groove portion), and the direction perpendicular to the paper surface is the extending direction of the molten solidified portion (groove portion).
[0075] In addition, the maximum value of the depth profile of the groove is preferably less than 0 μm, that is, the melt solidified portion does not protrude from the steel sheet surface. The reason for this is that if the melt solidified portion protrudes outward in the sheet thickness direction from the steel sheet surface, when the grain-oriented electromagnetic steel sheets are laminated as a transformer core, the space factor decreases and distortion is introduced into the steel sheet on the upper surface during lamination, resulting in deterioration of iron loss and noise. In addition, the maximum value of the depth profile of the groove is preferably greater than -d (μm), more preferably greater than -d / 2 (μm).
[0076] Furthermore, the interval between the molten solidified portions is preferably 1.0 mm or more and less than 5.0 mm. The reason is as shown in the above-mentioned experimental results. Moreover, the more preferable range of the interval between the molten solidified portions is also as shown in the above-mentioned experimental results.
[0077] Here, the interval between the molten solidified portions is the center-to-center distance between the molten solidified portions in the rolling direction.
[0078] In addition, the more the extension direction of the molten solidified portion is tilted from the sheet width direction (the direction perpendicular to the rolling direction), the fewer the magnetic poles generated at the interface between the closure domain and the main domain, and the worse the effect of refining the magnetic domains tends to be. Therefore, it is preferable that the angle between the extension direction of the molten solidified portion and the sheet width direction is within ±30°.
[0079] The composition of the grain-oriented electrical steel sheet according to an embodiment of the present invention is not particularly limited. For example, a preferred composition is as follows: C: 50 mass ppm or less, Si:2.0~8.0% by mass, Mn: 0.005~1.0% by mass, Al: 0.065% by mass or less, N: 0.0120% by mass or less, S: 0.030% by mass or less and Se: 0.030 mass% or less and Optionally, Contains one or more selected from the group consisting of Ni: 1.50 mass% or less, Sn: 1.50 mass% or less, Sb: 1.50 mass% or less, Cu: 3.0 mass% or less, P: 0.50 mass% or less, Mo: 0.10 mass% or less, and Cr: 1.50 mass% or less, The balance is Fe and unavoidable impurities. The preferred content of each element will be described below.
[0080] C: 50 mass ppm or less C can be contained in the slab to improve the hot-rolled sheet structure. However, in order to avoid the occurrence of magnetic aging during the manufacturing process, the C content contained in the slab is preferably reduced to 50 mass ppm or less by decarburization annealing, and the C content of the final product, the grain-oriented electrical steel sheet, is also equivalent to this. Therefore, the C content is preferably 50 mass ppm or less. The lower limit of the C content is not particularly limited, and may be 0 mass ppm.
[0081] Si:2.0~8.0% by mass Silicon is an element that is effective in increasing the electrical resistance of steel and improving core loss. Therefore, the Si content is preferably 2.0% by mass or more. However, if the Si content exceeds 8.0% by mass, there is a risk of deterioration in workability and threading property, and a decrease in magnetic flux density. Therefore, the Si content is preferably in the range of 2.0 to 8.0% by mass.
[0082] Mn:0.005~1.0% by mass Mn is an element useful for improving hot workability. Therefore, the Mn content is preferably 0.005% by mass or more. On the other hand, if the Mn content exceeds 1.0% by mass, there is a risk of a decrease in magnetic flux density. Therefore, the Mn content is preferably in the range of 0.005 to 1.0% by mass.
[0083] Al: 0.065% by mass or less, N: 0.0120% by mass or less, S: 0.030% by mass or less, and Se: 0.030% by mass or less As described later, the composition of the grain-oriented electrical steel sheet slab may be a composition using an inhibitor or a composition not using an inhibitor, but in either composition, the grain-oriented electrical steel sheet as the final product preferably contains Al: 0.065 mass% or less, N: 0.0120 mass% or less, S: 0.030 mass% or less, and Se: 0.030 mass% or less. Even in the case of a composition using an inhibitor, if purification is performed in the final annealing, the inhibitor components are removed. Therefore, the contents of these elements are more preferably Al: 0.010 mass% or less, N: 0.0050 mass% or less, S: 0.0050 mass% or less, and Se: 0.0050 mass% or less, respectively. The lower limit of the contents of these elements is not particularly limited and may be 0 mass%.
[0084] Optionally added components include at least one selected from the group consisting of Ni: 1.50 mass% or less, Sn: 1.50 mass% or less, Sb: 1.50 mass% or less, Cu: 3.0 mass% or less, P: 0.50 mass% or less, Mo: 0.10 mass% or less, and Cr: 1.50 mass% or less. Ni is an element effective for improving the hot-rolled sheet structure and enhancing the magnetic properties. Therefore, when Ni is contained, the content is preferably 0.03 mass% or more. However, when the Ni content exceeds 1.50 mass%, the secondary recrystallization becomes unstable and the magnetic properties may deteriorate. Therefore, when Ni is contained, the content is preferably 1.50 mass% or less.
[0085] In addition, Sn, Sb, Cu, P, Mo, and Cr are also elements that improve magnetic properties. Therefore, when these elements are contained, it is preferable that Sn: 0.01 mass% or more, Sb: 0.005 mass% or more, Cu: 0.03 mass% or more, P: 0.03 mass% or more, Mo: 0.005 mass% or more, and Cr: 0.03 mass% or more. However, if Sn: more than 1.50 mass%, Sb: more than 1.50 mass%, Cu: more than 3.0 mass%, P: more than 0.50 mass%, Mo: more than 0.10 mass%, and Cr: more than 1.50 mass%, the growth of secondary recrystallized grains is suppressed, and the magnetic properties may deteriorate. Therefore, when these elements are contained, it is preferable that Sn is 1.50 mass% or less, Sb is 1.50 mass% or less, Cu is 3.0 mass% or less, P is 0.50 mass% or less, Mo is 0.10 mass% or less, and Cr is 1.50 mass% or less.
[0086] The elements other than those mentioned above are Fe (iron) and unavoidable impurities.
[0087] The thickness of the grain-oriented electrical steel sheet according to an embodiment of the present invention is not particularly limited, but is preferably 0.15 mm or more and 0.30 mm or less.
[0088] In addition, in the grain-oriented electrical steel sheet according to an embodiment of the present invention, "having low iron loss, high magnetic permeability and good magnetostriction characteristics" means W 17 / 50 , ΔB8 and MHL 15 / 50 means that the pass criteria of the examples described later are simultaneously satisfied.
[0089] Next, an example of a method for manufacturing a grain-oriented electrical steel sheet according to an embodiment of the present invention will be described.
[0090] The steel material (slab) of the grain-oriented electrical steel sheet is hot-rolled to form a hot-rolled steel strip. The hot-rolled steel strip is then annealed. The hot-rolled steel strip is then cold-rolled once or twice or more times to form a cold-rolled steel strip (hereinafter also referred to as steel strip) of the final thickness. The steel strip is then decarburized and coated with an annealing separator mainly composed of MgO. The steel strip is then wound into a coil and subjected to final annealing for the purpose of secondary recrystallization and formation of a forsterite coating. The steel strip after the final annealing is then flattened, and a magnesium phosphate-based tension coating is formed to form a steel strip and a grain-oriented electrical steel sheet. The conditions of the hot rolling, hot-rolled sheet annealing, cold rolling, decarburization annealing, final annealing, and flattening annealing are not particularly limited, and may be performed according to conventional methods.
[0091] Furthermore, the composition of the steel material (slab) of the grain-oriented electrical steel sheet is not particularly limited as long as it is a composition that causes secondary recrystallization, but it is preferable that the composition be such that the above-mentioned preferred composition of the grain-oriented electrical steel sheet is obtained. for example, C: 0.08% by mass or less, Si:2.0~8.0% by mass, Mn:0.005~1.0% by mass Al: 0.065% by mass or less, N: 0.0120% by mass or less, S: 0.030% by mass or less and Se: 0.030 mass% or less and Optionally, Contains one or more selected from the group consisting of Ni: 1.50 mass% or less, Sn: 1.50 mass% or less, Sb: 1.50 mass% or less, Cu: 3.0 mass% or less, P: 0.50 mass% or less, Mo: 0.10 mass% or less, and Cr: 1.50 mass% or less, An example of the composition is a composition in which the balance is Fe and unavoidable impurities.
[0092] In addition, in the above-mentioned component composition, when an inhibitor is used, for example, when an AlN-based inhibitor is used, Al and N may be contained, and the preferable contents of Al and N are as follows. Al:0.010~0.065% by mass N:0.0050~0.0120% by mass When using a MnS·MnSe-based inhibitor, Se and / or S may be contained in addition to the above-mentioned Mn, and the preferred contents of S and Se are as follows: S:0.005~0.030% by mass Se:0.005~0.030 mass% In addition, both the AlN-based inhibitor and the MnS·MnSe-based inhibitor may be used in combination.
[0093] When no inhibitor is used, the preferred contents of Al, N, S and Se are as follows: Al: 0.010% by mass or less N: 0.0050% by mass or less S: 0.0050% by mass or less Se: 0.0050% by mass or less
[0094] C can be added to the slab to improve the hot-rolled sheet structure. However, in order to avoid the occurrence of magnetic aging during the manufacturing process, it is preferable to reduce the C content of the slab to 50 mass ppm or less by decarburization annealing. Therefore, the C content is preferably 0.08 mass% or less. Since secondary recrystallization occurs even without adding C, the lower limit of the C content is not particularly limited and may be 0 mass%.
[0095] The reasons for limiting the elements other than those mentioned above are basically the same as those for the composition of the grain-oriented electrical steel sheet described above, and therefore will not be explained here.
[0096] Then, in any of the steps after the above-mentioned cold rolling or between any of the steps, a treatment is performed to form a molten solidified portion on the surface of the grain-oriented electrical steel sheet (or steel strip). The method for forming the molten solidified portion is not particularly limited as long as it can form the above-mentioned molten solidified portion, and examples thereof include a method of irradiating an electron beam or a laser as an energy beam. Below, (A) the preferred conditions for irradiating an electron beam and (B) the preferred conditions for irradiating a laser are explained.
[0097] (A) Optimal conditions for electron beam irradiation To form a molten solidified portion on the surface of a grain-oriented electrical steel sheet, for example, it is effective to use an electron beam with high penetrating power. In particular, it is necessary to raise the temperature of the base material in the irradiated portion of the energy beam above its melting temperature to melt the base material to a certain depth, while controlling the irradiation conditions so as to prevent evaporation of the molten metal or to suppress it to a certain amount. Such control can be performed, for example, by setting the beam power density to 0.1 to 1.0 (J / mm) depending on the steel type and thickness of the grain-oriented electrical steel sheet. 2 ) and adjust each of the conditions below within the ranges shown below. In the case of electron beams, the beam power density is calculated as P / (v Φ) using the deflection speed v, the spot diameter Φ in the direction perpendicular to the scanning direction, and the electron beam power P. The electron beam power P is calculated as the acceleration voltage x beam current. For grain-oriented electrical steel sheets having the composition used in the examples described later, 0.1≦P(J / mm 2 )≦0.5, and a molten solidified portion can be formed in the range of 0.5 <P≦1.0(J / mm 2) within the range, a molten solidified portion and a groove portion defined by the molten solidified portion could be formed. However, even if the electron beam output P is within the above range, the amount of heat input and the temperature history change depending on the deflection speed v, the electron beam output P, and further the steel type and thickness of the grain-oriented electromagnetic steel sheet, so that only thermal strain may be introduced and the molten solidified portion may not be formed, or the molten metal may evaporate and the molten solidified portion may not be formed. Therefore, for example, it is preferable to perform a preliminary irradiation test or the like to determine appropriate irradiation conditions in advance according to the steel type and thickness of the grain-oriented electromagnetic steel sheet (the same applies to the case of laser irradiation described later).
[0098] In addition, the formation of the groove defined by the molten solidified portion and the control of the shape of the groove can be performed by adjusting the power density as described above, and further adjusting the spot shape so as to have a beam energy distribution of an ellipse, a line segment, or a point sequence shape having a major axis in the scanning direction. This can be expected to produce even higher effects.
[0099] Acceleration voltage: 60kV to 300kV A higher acceleration voltage is preferable because it increases the linearity of electrons and reduces the thermal effect on the outside of the beam irradiation area. For this reason, the acceleration voltage is preferably 60 kV or more. The acceleration voltage is more preferably 90 kV or more, and even more preferably 120 kV or more. On the other hand, if the acceleration voltage is too high, it becomes difficult to shield the X-rays generated by the electron beam irradiation. Therefore, from a practical point of view, the acceleration voltage is preferably 300 kV or less. The acceleration voltage is more preferably 200 kV or less.
[0100] Beam current: 0.5~40mA From the viewpoint of beam diameter, it is preferable that the beam current is small. This is because if the current is large, the beam diameter tends to expand due to Coulomb repulsion. Therefore, the beam current is preferably 40 mA or less. On the other hand, if the beam current is too small, there is a risk that the energy required to form distortion will be insufficient. Therefore, the beam current is preferably 0.5 mA or more.
[0101] - Vacuum level in the beam irradiation area The electron beam is scattered by gas molecules, which causes an increase in the beam diameter and halo diameter, a decrease in energy, etc. Therefore, the higher the degree of vacuum in the beam irradiation area, the better, and the pressure should preferably be 3 Pa or less. There is no particular lower limit, but if it is lowered too much, the cost of the vacuum system, such as the vacuum pump, will increase. Therefore, in practice, it is recommended to use a vacuum of 1×10 -5 It is preferable to set the pressure at 1 Pa or more.
[0102] -Spot diameter in the direction perpendicular to the scanning direction: 300μm or less The smaller the spot diameter, the more localized the distortion can be introduced, which is preferable. Therefore, the spot diameter of the energy beam in the direction perpendicular to the scan is preferably 300 μm or less. The spot diameter of the energy beam in the direction perpendicular to the scan is more preferably 280 μm or less, and further preferably 260 μm or less. Although the lower limit of the spot diameter of the energy beam in the direction perpendicular to the scan is not particularly limited, the spot diameter of the energy beam in the direction perpendicular to the scan is preferably, for example, 50 μm or more. The spot diameter refers to the full width at half maximum of the beam profile obtained by the slit method using a slit with a width of 30 μm.
[0103] Ratio of spot diameter in the scanning direction to the spot diameter in the direction perpendicular to the scanning direction (= [spot diameter in the scanning direction (μm)] ÷ [spot diameter in the direction perpendicular to the scanning direction (μm)]): More than 1 and 20 or less The closer the ratio of the spot diameter in the scanning direction to the spot diameter in the direction perpendicular to the scanning direction (hereinafter also referred to as the spot diameter ratio) is to 1, the more the heat input to the spot increases, and the easier it is to melt the steel sheet that is the base material. However, the concentration of the heat input area makes it easier for spatter to scatter, which may deteriorate the space factor when laminated as an iron core. There is also a risk of the groove becoming excessively deep. Therefore, the spot diameter ratio is preferably greater than 1, more preferably 1.5 or more, and even more preferably 2 or more. On the other hand, the heat input area increases as the spot diameter ratio increases. Therefore, although the scattering of spatter can be suppressed, the heat input energy required to melt the steel sheet increases. In this case, there is a concern that the burden on the transport system will increase in the case of a laser, and that the power supply capacity will increase in the case of an electron beam. Therefore, it is preferable that the spot diameter ratio is 20 or less.
[0104] As a method of realizing such a spot shape, for example, in the case of an electron beam, it is possible to focus the beam into spot shapes having different spot diameters by adjusting the magnetic field distribution in the focusing coil in the direction that exerts the Lorentz force in the scanning direction and the direction perpendicular to the scanning direction. In the case of a laser, a cylindrical lens can be placed on the beam path to adjust the spread of the beam in the scanning direction and the direction perpendicular to the scanning direction to form an elliptical shape, or a diffractive optical element can be placed on the beam path to focus the beam into an elliptical shape, a line segment shape, or a dot sequence shape.
[0105] ·Deflection speed: 5~400m / sec The slower the deflection speed of the energy beam, the more the amount of heat incident on the steel sheet per unit length can be increased. However, if the deflection speed of the energy beam is made too slow, spatters may adhere to the surface of the steel sheet due to scattering of metal vapor, and the space factor may deteriorate when laminated as an iron core. In addition, the depth of the groove may become excessive. Therefore, the deflection speed of the energy beam is preferably 5 m / sec or more. The deflection speed of the energy beam is more preferably 8 m / sec or more, and further preferably 10 m / sec or more. On the other hand, if the deflection speed of the energy beam is made too fast, a power supply capacity is required to provide the heat input required to melt the steel sheet, leading to an increase in the size of the equipment. Therefore, the deflection speed of the energy beam is preferably 400 m / sec or less.
[0106] (B) Optimal conditions for laser irradiation To form a molten and solidified portion on the surface of grain-oriented electrical steel sheet, it is effective to use, for example, a laser with a wavelength of 400 nm to 1200 nm, which has a high absorption rate in metal. In particular, it is necessary to raise the temperature of the base material in the energy beam irradiated portion above its melting temperature to melt the base material to a certain depth, while controlling the irradiation conditions so as to prevent evaporation of the molten metal or to suppress it to a certain amount. Such control can be performed, for example, at a range of 0.1 to 1.0 (J / mm) depending on the steel type and thickness of the grain-oriented electrical steel sheet. 2 ) and adjust the following conditions within the ranges shown below. In the case of a laser, the beam power density is expressed as P / (v Φ), where v is the scanning speed (deflection speed), Φ is the spot diameter, and P is the laser power.
[0107] In addition, the formation of the groove portion defined by the molten solidified portion and the control of the shape of the groove portion can be performed by adjusting the power density as described above, and further adjusting the spot shape so as to have a beam energy distribution of an ellipse, a line segment, or a point sequence having a major axis in the scanning direction. This can be achieved, and even greater effects can be expected.
[0108] Laser output: 50W or more and 5000W or less When the laser output is low, the scanning speed needs to be slowed down to melt the base material, the steel plate. However, if the scanning speed is slowed down too much, the space factor will decrease due to the scattering of spatter on the steel plate, and the manufacturing efficiency will deteriorate. In addition, the molten metal may evaporate, and the groove may become excessively deep. On the other hand, if the laser output is increased, the steel plate will be easily melted. However, damage to the laser transport system may increase, and the manufacturing efficiency may decrease due to the increased frequency of maintenance. Therefore, the laser output is preferably 50W or more and 5000W or less.
[0109] The preferred ranges of the spot diameter in the direction perpendicular to the scanning direction, the spot diameter ratio, and the scanning speed (deflection speed) are the same as those in (A) the preferred conditions for irradiating the electron beam, and therefore will not be described here.
[0110] The conditions for stress relief annealing performed after bending or the like on the grain-oriented electrical steel sheet can be exemplified by a nitrogen atmosphere, a treatment temperature of 800° C., and a treatment time of 3 hours. The grain-oriented electrical steel sheet according to an embodiment of the present invention has low core loss even after stress relief annealing, and also has high magnetic permeability and good magnetostriction characteristics, and can therefore be used extremely advantageously as an iron core material for transformers, particularly wound core transformers, etc.
[0111] The conditions other than those mentioned above are not particularly limited, and may be those according to conventional methods.
[0112] Next, the present invention will be specifically described based on the examples. The following examples are preferred examples of the present invention, and the present invention is not limited to these examples. The present invention can be modified within the scope of the present invention, and such modifications are also included in the technical scope of the present invention. EXAMPLES
[0113] Example 1 A slab of grain-oriented electrical steel sheet having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) was hot-rolled to obtain a hot-rolled steel strip. The hot-rolled steel strip was then subjected to hot-rolled sheet annealing. The hot-rolled steel strip was then subjected to two cold rolling processes with intermediate annealing in between to obtain a cold-rolled steel strip (hereinafter also referred to as steel strip) having a sheet thickness of 0.23 mm. The steel strip was then subjected to decarburization annealing and coated with an annealing separator mainly composed of MgO. The steel strip was then wound into a coil and subjected to final annealing for the purpose of secondary recrystallization and formation of a forsterite coating.
[0114] [Table 1]
[0115] Next, the steel strip was subjected to flattening annealing, and then one side of the steel strip was irradiated with an electron beam or a laser to form a linear molten solidified portion. At this time, the irradiation conditions, specifically, the power density (accelerating voltage, beam current, laser output, and deflection speed) were variously changed. In addition, the spot shape was an ellipse, and the ratio of the spot diameter was variously changed. Note that both the electron beam and the laser irradiation were performed at intervals of 4 mm in the rolling direction. In addition, a non-irradiated region of the beam was provided in a part of the steel strip.
[0116] Next, a magnesium phosphate-based tension coating was formed on the steel strip to obtain the final product, a grain-oriented electrical steel sheet. Note that the conditions other than those specified in each of the above steps were the same as in the conventional method. Furthermore, the chemical compositions of the final steel strips all satisfied the preferred chemical compositions of the grain-oriented electrical steel sheet according to one embodiment of the present invention described above.
[0117] The steel strip thus obtained was subjected to a heat treatment simulating stress relief annealing (nitrogen atmosphere, treatment temperature: 800°C, treatment time: 3 hours). Next, a sample was cut out from the area where the linear molten solidified part of the steel strip was formed, embedded in a mold, and mirror polished, and then the strain distribution in the rolling direction cross section of the sample was obtained by the EBSD Wilkinson method. Then, from the strain distribution of each sample obtained, ΔE was calculated using the above formulas (1) to (4) to create a distribution of anisotropic energy, and the deepest position of each sample where ΔE<0 and the deepest position where ΔE≦-2 were obtained.
[0118] In addition, for each sample, B8 and W were measured by the Epstein method described in JIS C2550. 17 / 50 Furthermore, a reference sample (a sample that has not been subjected to magnetic domain refinement treatment) was cut out from the non-irradiated area of the steel strip, and B8 and W were measured by the Epstein method described in JIS C2550. 17 / 50 Then, ΔB8 (= [B8 measured on a sample cut from the area where a linear molten solidification part was formed on the steel strip] - [B8 measured on a reference sample]) was calculated as an index of the change in magnetic permeability.
[0119] In addition, the magnetostrictive vibration waveform of each sample was measured using a laser Doppler magnetostrictive vibrometer when it was magnetized with a 1.5T, 50Hz sinusoidal AC current. The measured magnetostrictive vibration waveform was then Fourier-decomposed into vibration acceleration components with frequencies of every 100Hz. Next, the values of each frequency component, which were weighted for hearing on the A scale, were integrated from 0 to 1000Hz, and the integrated values were used as magnetostrictive harmonics MHL, which are an index of magnetostrictive properties. 15 / 50 It was decided.
[0120] Next, a model three-phase winding transformer (core weight 500 kg) was made using each sample, and the transformer iron loss was measured when the magnetic flux density in the core legs was 1.7 T at a frequency of 50 Hz. The no-load loss of this transformer iron loss was measured using a wattmeter. At the same time, this model transformer was excited in a soundproof room under conditions of maximum magnetic flux density Bm = 1.7 T and frequency of 50 Hz, and the sound level (dBA) of the transformer was measured using a sound level meter. Hereinafter, the sound level of the transformer will also be referred to as the transformer noise.
[0121] For comparison, a steel strip (No. 33) was prepared without forming a molten solidified portion (without performing magnetic domain refinement treatment), and a steel strip (No. 34) was prepared in which a groove 20 μm deep was formed by laser irradiation. 17 / 50 , ΔB8, MHL 15 / 50 The transformer iron loss and transformer noise were measured. Note that no groove was formed in any of the steel strips except for No. 34.
[0122] The above results are summarized in Table 2. The presence or absence of the molten solidified portion was confirmed by the above-mentioned method. 17 / 50 , ΔB8, MHL 15 / 50 The evaluation criteria for transformer iron loss and transformer noise are as follows: ·W 17 / 50 ◎ (Pass, especially excellent): Iron loss improvement amount ΔW 17 / 50 is 0.08W / Kg or more 〇(Pass, Excellent): Iron loss improvement amount ΔW 17 / 50 is 0.05W / Kg or more (except for the cases of ◎) ×(Fail): Iron loss improvement amount ΔW 17 / 50 is less than 0.05W / Kg Here, the iron loss improvement amount ΔW 17 / 50 is the improvement in iron loss before and after the magnetic domain refinement process, and [W measured on the reference sample 17 / 50 ]-[W measured on the sample 17 / 50 ] is calculated. ΔB8 ◎ (Pass, particularly excellent): -0.0006T or more 〇 (Pass, Excellent): -0.0010T or more (except for ◎) × (Fail): -0.0010T or less Here, ΔB8 is the change in B8 before and after the magnetic domain refinement process, and is calculated as [B8 measured on the sample]-[B8 measured on the reference sample]. ·MHL 15 / 50 ◎ (Pass, particularly excellent): 26.0 dBA or less 〇 (Pass, Excellent): 27.5 dBA or less (except for ◎) ×(Fail): More than 27.5dBA Transformer core loss ◎ (Pass, particularly excellent): Transformer iron loss improvement of 0.08W / Kg or more 〇 (Pass, Excellent): Transformer iron loss improvement of 0.05W / Kg or more (except for ◎) × (Failed): The improvement in transformer core loss is less than 0.05W / Kg Here, the improvement in transformer iron loss is the improvement in transformer iron loss before and after magnetic domain refinement processing, [W measured with a model transformer made from a reference sample] 17 / 50 ]-[W measured using a model transformer made from the sample 17 / 50 ] is calculated. Transformer noise ◎ (Pass, particularly excellent): 32.0 dBA or less 〇 (Pass, Excellent): 33.5 dBA or less (except for ◎) ×(Fail): More than 33.5dBA
[0123] [Table 2]
[0124] As can be seen from Table 2, all of the examples of the invention have low iron loss, high magnetic permeability, and good magnetostriction characteristics. In addition, the transformer iron loss and transformer noise measured using a model transformer made from the sample of the example of the invention were both low and reached the target level. Furthermore, the examples of the invention in which the deepest position of ΔE≦-2 was 4 μm to 40 μm obtained particularly excellent characteristics.
[0125] On the other hand, none of the comparative examples were able to achieve low core loss, high magnetic permeability, and favorable magnetostriction characteristics.
[0126] Example 2 A slab of grain-oriented electrical steel sheet having the composition shown in Table 3 (the balance being Fe and unavoidable impurities) was hot-rolled to obtain a hot-rolled steel strip. The hot-rolled steel strip was then subjected to hot-rolled sheet annealing. The hot-rolled steel strip was then subjected to two cold rolling processes with intermediate annealing in between to obtain a cold-rolled steel strip (hereinafter also referred to as steel strip) having a sheet thickness of 0.23 mm. The steel strip was then subjected to decarburization annealing and coated with an annealing separator mainly composed of MgO. The steel strip was then wound into a coil and subjected to final annealing for the purpose of secondary recrystallization and formation of a forsterite coating.
[0127] [Table 3]
[0128] Next, after the steel strip was subjected to flattening annealing, a laser was irradiated on one side of the steel strip in the rolling direction to form a linear molten solidified portion. At this time, the irradiation conditions, specifically, the power density (accelerating voltage, beam current, laser output, and deflection speed) were variously changed. In addition, the spot shape was made into a line segment shape using a diffractive optical element, and the line segment length was adjusted to variously change the spot diameter ratio. In addition, the laser irradiation was performed at intervals of 0.5 to 7.0 mm in the rolling direction in all cases. In addition, a non-irradiated region of the beam was provided in a part of the steel strip.
[0129] Next, a magnesium phosphate-based tension coating was formed on the steel strip to obtain the final product, a grain-oriented electrical steel sheet. Note that the conditions other than those specified in each of the above steps were the same as in the conventional method. Furthermore, the chemical compositions of the final steel strips all satisfied the preferred chemical compositions of the grain-oriented electrical steel sheet according to one embodiment of the present invention described above.
[0130] The steel strip thus obtained was subjected to a heat treatment simulating stress relief annealing (nitrogen atmosphere, treatment temperature: 800°C, treatment time: 3 hours). Next, in the same manner as in Example 1, the distribution of anisotropic energy was created, and the deepest position where ΔE<0 and the deepest position where ΔE≦-2 were determined for each sample. In addition, for each sample, W 17 / 50 , ΔB8, MHL 15 / 50, transformer iron loss and transformer noise were measured.
[0131] Further, in the same manner as described above, a depth profile of the grooves of each sample was created, and the depth d (μm) of the deepest point of the grooves, the number N of minimum values, and d / W×100 (%) were determined.
[0132] Furthermore, for comparison, a steel strip (No. 58) was prepared without forming a molten solidified portion (without performing magnetic domain refinement treatment), and a steel strip (No. 59) was prepared in which a groove 20 μm deep was formed by laser irradiation. 17 / 50 , ΔB8, MHL 15 / 50 , transformer iron loss and transformer noise were measured.
[0133] The above results are summarized in Table 4. The presence or absence of the molten solidified portion was confirmed by the above-mentioned method. 17 / 50 , ΔB8, MHL 15 / 50 The evaluation criteria for the transformer iron loss and transformer noise are the same as in Example 1, but the iron loss change amount ΔW 17 / 50 , ΔB8, MHL 15 / 50 , transformer iron loss change ΔW 17 / 50 When the transformer noise simultaneously satisfies the following ranges, it can be said that extremely excellent characteristics have been obtained. ΔW 17 / 50 : 0.14W / kg or more (especially 0.15W / kg or more) ΔB8: -0.0002T or more (especially -0.0001T or more) ·MHL 15 / 50 : 26.0dBA or less (especially 25.5dBA or less) Transformer iron loss ΔW 17 / 50 : 0.16W / kg or more (especially 0.17W / kg or more) Transformer noise: 32.0dBA or less (especially 31.5dBA or less)
[0134] [Table 4] TIFF0007639805000014.tif255126
[0135] As can be seen from Table 4, all of the examples of the invention have low iron loss, high magnetic permeability, and good magnetostriction characteristics. In addition, the transformer iron loss and transformer noise measured using a model transformer made from the samples of the examples of the invention were both low and reached the target levels. Furthermore, ΔE (KJ / m 3 ) is -2KJ / m 3 In the example of the invention in which the deepest position of the region below 4 μm is 4 μm to 40 μm, there is a groove defined by the molten solidified portion, the depth d of the deepest point of the groove is less than 8.0 μm, the number N of minimum values is 2 or more, d / W×100(%) is 5% or more and less than 20%, and the spacing of the molten solidified portion is 1.0 mm or more and less than 5.0 mm, extremely excellent characteristics were obtained.
[0136] On the other hand, none of the comparative examples were able to achieve low core loss, high magnetic permeability, and favorable magnetostriction characteristics.
Claims
1. A grain-oriented electrical steel sheet, The grain-oriented electrical steel sheet has, on one surface thereof, periodically linear molten and solidified portions that cross the rolling direction, In the distribution of anisotropic energy from the surface of the molten solidified portion in the rolling direction cross section of the grain-oriented electrical steel sheet to the sheet thickness direction, ΔE (KJ / m 3 The deepest position of the region where the σ is negative is 4 μm or more and 150 μm or less from the surface of the molten solidified portion. Here, ΔE is defined by the following formula (1). ΔE=E sub -E RD ・・・(1) In formula (1), E RD (KJ / m 3 ) and E sub (KJ / m 3 ) are the anisotropy energy in the rolling direction, and the anisotropy energy in the crystal [010] orientation or [100] orientation when the crystal [001] orientation is the rolling direction, respectively, and are calculated by the following formulas (2) to (4). [0010] [0025] [0030] In formulas (2) to (4), σ RD , σ TD and σ ND are the residual stresses in the rolling direction, the width direction, and the thickness direction, respectively. ε RD , ε TD and ε ND are the strains in the rolling direction, width direction, and thickness direction, respectively.
2. In the distribution of the anisotropic energy, the ΔE (KJ / m 3 ) is -2KJ / m 3 The grain-oriented electrical steel sheet according to claim 1, wherein the deepest position of the region below is 4 μm to 40 μm away from the surface of the molten solidified portion.
3. The grain-oriented electrical steel sheet according to claim 1 , further comprising a groove defined by the molten solidified portion.
4. The grain-oriented electrical steel sheet according to claim 2 , further comprising a groove defined by the molten solidified portion.
5. The grain-oriented electrical steel sheet according to claim 3, wherein in a depth profile of the groove, a depth d of the deepest point of the groove is less than 8.0 µm.
6. 5. The grain-oriented electrical steel sheet according to claim 4, wherein in a depth profile of the groove, a depth d of the deepest point of the groove is less than 8.0 μm.
7. In the depth profile of the groove, there are two or more minimum values; The grain-oriented electrical steel sheet according to any one of claims 3 to 6, wherein d / W×100(%), which is a ratio of a depth d of the deepest point of the groove to a width W of the groove, is 5% or more and less than 20%.
8. The grain-oriented electrical steel sheet according to any one of claims 1 to 6, wherein the interval between the molten solidified portions in the rolling direction is 1.0 mm or more and less than 5.0 mm.
9. The grain-oriented electrical steel sheet according to claim 7, wherein the interval between the molten solidified portions in the rolling direction is 1.0 mm or more and less than 5.0 mm.
Citation Information
Patent Citations
Device for straining steel plate
JP1987086121A
Small sized panhead device
JP1994022179A
Low iron loss grain-oriented silicon steel sheet and its production
JP1994212275A
Manufacture of low iron-loss grain oriented silicon steel plate and plasma generating device
JP1995192891A
Method for manufacturing grain-oriented electromagnetic steel sheet with low core loss
JP2003129135A